(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was carried out to access on the present status of Indian major carp broodstock management, suggests some guidelines to control negative selection and inbreeding in hatchery stocks in Jessore, Bangladesh. The survey was conducted in 20 hatcheries at Chacrha in Jessore from November, 2013 to October, 2014. Information showed that brood fish selection for induced breeding was done on the basis of their experience. The sources of brood fish were mainly own and other sources were Halda River, Padma River, Govt. brood bank, world fish center and BFRI. Feed ingredients used as rice bran (39%), mustard oil cake (29%), vitamin and mineral premix (3%), wheat flour (7%), fish meal (13%) and soyabean flour (5%). Nutritional compositions of feed were protein (20-30%), lipid (10-12%), carbohydrate (25-35%) and fat (7-11%). Fertilizer such as TSP (0.484 kg/decimal), urea (0.242 kg/decimal), cowdung (6.5 kg/decimal), poultry dropping (3 kg/decimal) and MP (0.181 kg/decimal) were used. Hatching rate was 85-91% and deformed hatchlings were 5-7% in the hatcheries. Both positive (63%) and negative (37%) selection were identified. Anchor worm (Lernaeasis) disease was the most harmful problem of which solution was not given by them. Hatcheries owners assumed that if they would use wild brood fish, inbreeding could be removed and thus survival and growth of fry could be increased. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 362-370